A meta analysis of Chinese medicine combined with glucocorticoid in the treatment of IgA nephropathy - JIN Shan-shan; ZHU Guo-shuang; WANG Xiao-qin (Linchuang shenzangbing zazhi)
Objective To systematically evaluate the efficacy of Chinese medicine combined with glucocorticoid in the treatment of IgA nephropathy,so as to guide the clinical practice better.Methods The randomized controlled trials(RCTs)about TCM combined with glucocorticoid from the IgA nephropathy-related literatures were searched from CNKI,Wan Fang,VIP,Chinese biomedical literature database,Pubmed,Cochrane Library,Embase database.Meta analysis was performed on total efficiency,complete remission rate,24-h urinary protein quantity,serum creatinine and so on using Review Manager 5.3 software.The quality of retrieval literature was evaluated according to Cochrane Collaboration standard and Jadad quality score method.Results According to the search results and inclusion and exclusion criteria,a total of 12 RCTs were included,totally 840 patients.The treatment group of Chinese medicine combined with glucocorticoid was more effective than that in the simple glucocorticoid therapy group [OR=3.36,95%CI(2.30,4.91),P<0.000 01],and the rate of complete remission was higher in the combined group[OR=2.73,95%CI(2.02,3.69),P<0.000 01].24-h urinary protein quantity[MD=-0.18,95%CI(-0.21,-0.16),P<0.000 01],and serum creatinine[MD=-10.13,95%CI(-12.11,-8.14),P<0.00001]were decreased more significantly in the combined group as compared with those in the simple group.The quality of the literature included in the meta analysis was generally high.The heterogeneity of the total effective rate and complete remission rate was low.The heterogeneity test revealed that I2>50%in the24-h urine protein quantity and serum creatinine between two groups,were both,but the funnel map was basically symmetrical,suggesting that although there was a certain heterogeneity,the results were credible.Conclusions This systematic review provides evidence that Chinese medicine combined with glucocorticoid is more effective than steroid alone in the treatment of IgA nephropathy.